Christian Higher Education's Place within Private Higher Education - Levy, Daniel (International Higher Education, 2017)
Universities sponsored by Christian churches are a neglected but important part of private higher education everywhere. Christian higher education is rapidly expanding in Africa particularly. This article discusses the nature of expansion as well as the challenges facing Christian higher education worldwide.